2008
DOI: 10.1093/nar/gkn328
|View full text |Cite
|
Sign up to set email alerts
|

The Zur of Xanthomonas campestris functions as a repressor and an activator of putative zinc homeostasis genes via recognizing two distinct sequences within its target promoters

Abstract: It has been long considered that zinc homeostasis in bacteria is maintained by export systems and uptake systems, which are separately controlled by their own regulators and the uptake systems are negatively regulated by Zur which binds to an about 30-bp AT-rich sequence known as Zur-box present in its target promoters to block the entry of RNA polymerase. Here, we demonstrated in vivo and in vitro that in addition to act as a repressor of putative Zn2+-uptake systems, the Zur of the bacterial phytopathogen Xa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
56
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 44 publications
1
56
0
1
Order By: Relevance
“…This can be excluded in this study, as we identified Zur boxes in the upstream regions of both Zur-activated genes. Only in one other study, of the phytopathogen Xanthomonas campestris, did Zur act as a direct activator of one gene (22).…”
Section: Discussionmentioning
confidence: 96%
“…This can be excluded in this study, as we identified Zur boxes in the upstream regions of both Zur-activated genes. Only in one other study, of the phytopathogen Xanthomonas campestris, did Zur act as a direct activator of one gene (22).…”
Section: Discussionmentioning
confidence: 96%
“…Coelibactin, a putative zincophore, has been recently reported to be regulated by Zur in Streptomyces coelicolor (13,14). In addition, Zur can also act as a direct activator to induce a zinc-export system in Xanthomonas campestris (15).…”
mentioning
confidence: 99%
“…This was not the case. In X. campestris Zur controls the expression of both zinc uptake and efflux; thus, when Zur is absent, X. campestris not only undergoes unregulated uptake of zinc, but it also fails to activate zinc efflux systems (19). Our data suggest that, unlike X. campestris Zur, C. diphtheriae Zur is not required for the activation of zinc efflux.…”
Section: Discussionmentioning
confidence: 75%